Hypoxia-Independent Drivers of Melanoma Angiogenesis - Meierjohann, Svenja (Frontiers in Oncology, 2015)
Tumor angiogenesis is a process which is traditionally regarded as the tumor`s response to low nutrient supply occurring under hypoxic conditions. However, hypoxia is not a prerequisite for angiogenesis. The fact that even single tumor cells or small tumor cell aggregates are capable of attracting blood vessels reveals the early metastatic capability of tumor cells. This review sheds light on the hypoxia independent mechanisms of tumor angiogenesis in melanoma.